Applications Know Preparation for Earthquakes for Elementary School Students - Rian Farta Wijaya; Ataya Putri; Hermansyah Hermansyah; Nova Mayasari; Rio Septian Hardinata; Moch. Iswan Perangin-angin (Journal of Applied Engineering and Technological Science (JAETS), 2022)
This research is entitled the application of recognizing preparation for earthquakes for elementary school students. The goal is to produce an application that can help students recognize preparation for earthquakes. The resulting application is made using Adobe Flash CS 6, and the Actionscript 3 programming language. This application can run well on Android smartphones, and personal computers/laptops. There were 20 students who were the subjects of this study, and they came from elementary schools Negeri 105270 Pujimulio, Deli Serdang, North Sumatra. Students who are tested beforehand (pre-test) their knowledge about preparation in dealing with earthquakes. After that students are asked to use the resulting application. After that, students are tested again for their knowledge (post test). So from the pre test and post test carried out, get test results that show an increase in students' knowledge in learningknow how to prepare for an earthquake.